FACTORS INFLUENCING THE UTILIZATION OF HEALTH SERVICES BY NATIONAL HEALTH INSURANCE PARTICIPANTS AT THE BATANG KUIS COMMUNITY HEALTH CENTER - Riska Ananda; Fitriani Pramita Gurning; Eliska Eliska (Journal of World Future Medicine, Health and Nursing, 2026)
Universal Health Coverage in Deli Serdang Regency has reached 98.6%. However, JKN participant activity and primary health care utilization in several areas remain below the national target. At UPT Puskesmas Batang Kuis, JKN utilization by participants has reached only 67.2% of total users. This study modifies Andersen’s theoretical model by incorporating contemporary digitalization indicators (use of the Mobile JKN application and digital queue system) within the knowledge assessment instrument. It aims to analyze factors associated with health service utilization among JKN participants. This quantitative study used a cross-sectional design with 96 respondents selected through simple random sampling. Data were collected using a structured questionnaire tested for validity and reliability, then analyzed using the chi-square test and binary logistic regression. Univariate analysis showed that 51.0% of respondents utilized health services. Individual assessment of the health center was the dominant factor (Exp(B)=13.741). Positive attitudes, family support, and good perceptions of facility quality were the main determinants, while knowledge alone was insufficient. Health centers should improve physical service quality, staff responsiveness, and medicine availability.